Glycated Albumin Value and Its Relation with The Improvement of Diabetic Ulcers: Pilot Study - Nur Rosyid, Fahrun; Heri Nugroho H S, K; ., Muhtadi; ., Sugiyarti (KnE Social Sciences, 2023)
Diabetic ulcer refers to a complication of chronic hyperglycaemia. When treating hyperglycaemia, it is necessary to well and immediately monitor the average level of glucose, i.e. glycated albumin (GA) value. This study investigated the correlation between GA values and the improvement of diabetic ulcers. A clinical, cross-sectional study. Thirty patients with Diabetic Foot Ulcer (DFU) were involved as the subjects of this study and they were selected by accidental sampling with the following criteria: (1) patients with Type 2 DM with DFU according to grade 2 and 3 PEDIS degrees; (2) aged 30-60 years; (3) diagnosis criteria for DM and DM type 2 in accordance to the American Diabetes Association 2012; (4) IMT value: 18.5-22.9. Data collection technique was by checking GA levels, while monitoring the improvement of diabetic ulcers was by using PEDIS degrees. Meanwhile, data analysis used Spearman’s rho. The results of this study showed that most of research subjects had the values of GA failure with PEDIS 2 degree, i.e. 8 (26.7%) and there was no normal GA value with the degree of PEDIS 1, 2 and 3. There was a significant correlation between GA values and PEDIS degree (p = 0.001, p < 0.05). The findings revealed a correlation of GA values and improvement in diabetes ulcers. GA control is needed for the improvement of diabetes ulcers under nursing care. Keywords: Glycated Albumin; diabetic ulcers; DFU; chronic hyperglycaemia